2014
DOI: 10.1097/ico.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-biochemical Correlation of the Effect of Subconjunctival Bevacizumab for Corneal Neovascularization

Abstract: Subconjunctival bevacizumab helps to regress CNV due to a decrease in corneal VEGF levels and might prove beneficial for use in clinical conditions leading to CNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
7
2
1
Order By: Relevance
“…7 However, In another study regression of corneal neovascularization was observed in 66.7% (8/12 patients). 8 So findings this study not match with our study.…”
Section: Resultscontrasting
confidence: 91%
“…7 However, In another study regression of corneal neovascularization was observed in 66.7% (8/12 patients). 8 So findings this study not match with our study.…”
Section: Resultscontrasting
confidence: 91%
“…(Table-III However, In another study regression of corneal neovascularization was observed in 66.7% (8/12 patients). 8 So findings this study not match with our study.…”
Section: Resultscontrasting
confidence: 57%
“…Subsequently, the same group showed that subconjunctival injection of bevacizumab (2.5 mg/0.1 ml) was more effective than the topical application in reducing corneal neovascularization. 3,16 Other studies have used either subconjunctival injection or a combination of subconjunctival injection and topical application as discussed below.…”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 99%